Evaluating a new method for reconstructing forest conditions from General Land Office survey records. Issue 5 (24th May 2017) - Levine, Carrie R.; Cogbill, Charles V.; Collins, Brandon M.; Larson, Andrew J.; Lutz, James A.; North, Malcolm P.; Restaino, Christina M.; Safford, Hugh D.; Stephens, Scott L.; Battles, John J.
Abstract: Historical forest conditions are often used to inform contemporary management goals because historical forests are considered to be resilient to ecological disturbances. The General Land Office (GLO) surveys of the late 19th and early 20th centuries provide regionally quasi‐contiguous data sets of historical forests across much of the Western United States. Multiple methods exist for estimating tree density from point‐based sampling such as the GLO surveys, including distance‐based and area‐based approaches. Area‐based approaches have been applied in California mixed‐conifer forests but their estimates have not been validated. To assess the accuracy and precision of plotless density estimators with potential for application to GLO data in this region, we imposed a GLO sampling scheme on six mapped forest stands of known densities (159–784 trees/ha) in the Sierra Nevada in California, USA, and Baja California Norte, Mexico. We compared three distance‐based plotless density estimators (Cottam, Pollard, and Morisita) as well as two Voronoi area (VA) estimators, the Delincé and mean harmonic Voronoi density (MHVD), to the true densities. We simulated sampling schemes of increasing intensity to assess sampling error. The relative error (RE) of density estimates for the GLO sampling scheme ranged from 0.36 to 4.78. The least biased estimate of tree density in every stand was obtained with the Morisita estimator and the most biased was obtained with the MHVD estimator. The MHVD estimates of tree density were 1.2–3.8 times larger than the true densities and performed best in stands subject to fire exclusion for 100 yr. The Delincé approach obtained accurate estimates of density, implying that the Voronoi approach is theoretically sound but that its application in the MHVD was flawed. The misapplication was attributed to two causes: (1) the use of a crown scaling factor that does not correct for the number of trees sampled and (2) the persistent underestimate of the true VA due to a weak relationship between tree size and VA. The magnitude of differences between true densities and MHVD estimates suggest caution in using results based on the MHVD to inform management and restoration practices in the conifer forests of the American West.